Prototype quick reference - Raymond, Scott (O'Reilly short cuts., 2006)
This short cut provides a complete quick reference to the Prototype JavaScript framework. Prototype is an open-source library that is particularly useful to developers of dynamic Ajax applications, and to other web developers who need to work with DOM elements. If you're a web developer building sophisticated, user-friendly applications, you should be using Prototype. This reference gives you everything you need to use Prototype to its fullest. This document covers Prototype 1.4. There will be a free upgrade to the Prototype 1.5 version of this document.